Fostering innovative product development for neglected tropical diseases through partnerships. (2016) - Starr, Amy; Graef, Katy M; Dent, Jennifer
Neglected tropical diseases are a group of infectious diseases that threaten and impact a significant portion of individuals living in low- and middle-income countries. Healthcare product R&D, which has been relatively limited for this group of infectious diseases, is timely and requires significant risk and resource investment by companies. Regardless of these costs, the global community has recognized the impact on human health that developing products for these diseases could have. Incentives, including 'push' and 'pull' funding, and platforms that support sharing of intellectual property through partnerships, such as The World Intellectual Property Organization Re:Search, are driving R&D. These mechanisms entice more organizations to participate in global health product development activities, and combine assets and capabilities while reducing costs and risk.